Further evidence for the development of photic-zone euxinic conditions during Mesozoic oceanic anoxic events - Pancost, R; Crawford, N; Magness, S; Turner, A; Jenkyns, H; Maxwell, JR (2004)
Periods in Earth history characterized by extensive organic carbon deposition, so-called oceanic anoxic events (OAEs), are the subject of considerable scrutiny. Insight into the extent of anoxic conditions in the water column has been provided by the reported occurrence of derivatives of isorenieratene, a carotenoid found only in green sulphur bacteria and thus indicative of photic-zone euxinia (i.e. a water column containing free H2S), in North Atlantic deep-sea sediments deposited during the Cenomanian-Turonian boundary OAE2 (Bonarelli Event). In this study, we have used the distributions of chlorophyll and bacteriochlorophyll degradation products, maleimides (1-H-pyrrole-2,5-diones) and high molecular weight porphyrins, to examine further the Cenomanian-Turonian boundary OAE2 as well as other OAEs of the early Toarcian (Posidonienschiefer Event) and early Aptian (Selli Event). In particular, methyl isobutyl (Me,i-Bu) maleimide, on structural grounds, appears to be diagnostic of green sulphur bacteria. This compound occurs in five of seven examined marls that record the early Toarcian OAE (Marche-Umbria, Italy), further expanding the geographical range of Toarcian sediments where evidence for photic-zone euxinic conditions has been found. Me,i-Bu maleimide occurs in three of six black shales spanning the Livello Selli (Marche-Umbria, Italy), the type locality for the Aptian OAE1a, providing the first evidence for photic-zone euxinic conditions during this event. With respect to the Cenomanian-Turonian OAE, maleimide evidence for photic-zone euxinic conditions was found in all the North Atlantic sites investigated including those characterized by relatively organic-lean sediments, several Tethyan sites and one site off western Australia. These data indicate that euxinic conditions were common in the water column during Mesozoic oceanic anoxic events.